Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Spawning patterns provide further evidence for multiple stocks of sardine ( Sardinops sagax ) off eastern Australia - Stuart C. Sexton; Tim M. Ward; John Stewart; Kerrie M. Swadling; Charlie Huveneers (Fisheries Oceanography, 2019)
Previous studies have suggested that sardine, Sardinops sagax , off eastern Australia spawns across its entire range when habitat conditions are suitable. However, recent studies have suggested that separate sub‐populations and spawning groups may occur in the region. Spawning patterns off eastern Australia were investigated using data collected during nine ichthyoplankton surveys conducted between 1997–2015, and adult reproductive data obtained from ad hoc commercial sampling off New South Wales ( NSW ). The egg surveys covered the known distribution of sardine off eastern Australia and included year‐round sampling in the northern and southern parts of this range. Egg distributions and analysis of gonadosomatic indices identified two spatio‐temporally separate spawning groups; one occurring off southern Queensland to northern NSW during late winter and early spring, and a smaller group off eastern Tasmania to southern NSW during summer. Most eggs were collected from waters 50–90 m deep, with sea surface temperatures of 18–23°C. Additive modelling indicated depth was the most significant factor driving selection of spawning habitat, followed by the interaction of month and latitude. Low egg densities were recorded in waters between 34–37°S, despite conditions within the ranges suitable for spawning. The presence of two spawning groups of sardine off eastern Australia supports recent findings that two sub‐populations occur in the region. Findings of this study will help to optimise the spatio‐temporal extent of future egg surveys and further confirm the need to coordinate future management of each sub‐population among relevant jurisdictions.

Integrated approach to determining stock structure: implications for fisheries management of sardine, Sardinops sagax, in Australian waters - Christopher Izzo; Tim M. Ward; Alex R. Ivey; Iain M. Suthers; John Stewart; Stuart C. Sexton; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2017)